Modulation of Ion Channels in the Superior Cervical Ganglion Neurons by Myocardial Ischemia and Fluvastatin Treatment - Cheng, Lijun; Wang, Xinghua; Liu, Tong; Tse, Gary; Fu, Huaying; Li, Guangping (Frontiers in Physiology, 2018)
Background Superior cervical ganglion (SCG) in the autonomic nervous system played an important role in regulation of cardiovascular diseases. The aim of the present study was to investigate the effects of different ischemia time and fluvastatin on the characteristics of SCG neurons in a rabbit myocardial ischemic (MI) model. Methods The MI model in rabbit was induced by abdominal subcutaneous injections of isoproterenol (ISO). By using whole-cell patch-clamp technique, we studied the characteristic change of potassium channel current (IK), sodium channel current (INa) and action potentials (AP) on isolated SCG neuron cells in control group, MI 7 d group, MI 14 d group, Fluvastatin 7 d group (Fluvastatin pre-treated 14 d and treated 7 d after ISO-induced MI) and Fluvastatin 14 d group (Fluvastatin pre-treated 14 d and treated 14 d after ISO-induced MI) respectively. In addition, the RNA expression of KCNQ3 and SCN9A protein in SCG tissue were determined by real-time PCR. Intracellular calcium concentration was monitored using co focal laser scanning microscope. Results Compared with control group, the current amplitude of the IK and INa were increased in MI 7 d and MI 14 d group. KCNQ3 RNA (RNA corresponding to channel proteins of IK) expression and SCN9A RNA (RNA corresponding to channel proteins of INa) expression were also increased in MI groups. And activation curves and recovery curves after inactivation of INa in two MI groups shifted toward negative potential compared with the control group. Treatment with fluvastatin in two MI group reversed the changes. Intracellular calcium concentration in SCG neuron cells were not changed significantly in MI group and in fluvastatin-treated group. AP amplitude was increased and APD90 was shortened in MI 7 d and MI 14 d group. These changes were reversed in the fluvastatin-treated MI group. Conclusion Fluvastatin treatment partly reversed characteristics of SCG neuron cells in MI. It could be one of the potential targets of fluvastatin in treating coronary heart diseases.